Nurse Scheduling Using Mathematical Programming - Miller, Holmes E.; Pierskalla, William P.; Rath, Gustave J. (Operations Research, 1976)
This paper formulates the nurse-scheduling problem as one of selecting a configuration of nurse schedules that minimize an objective function that balances the trade-off between staffing coverage and schedule preferences of individual nurses, subject to certain feasibility constraints on the nurse schedules. The problem is solved by a cyclic coordinate descent algorithm. We present results pertaining to a six-month application to a particular hospital unit and draw comparisons between the algorithm and hospital-generated schedules.